Brain Vital Signs in Elite Ice Hockey: Towards Characterizing Objective and Specific Neurophysiological Reference Values for Concussion Management - Carrick, Frederick R.; Pagnacco, Guido; Azzolino, Sergio F.; Hunfalvay, Melissa; Oggero, Elena; Frizzell, Tory; Smith, Christopher J.; Pawlowski, Gabriela; Campbell, Natasha K. J.; Fickling, Shaun D.; Lakhani, Bimal; D’Arcy, Ryan C. N. (Frontiers in Neuroscience, 2021)
Background: Prior concussion studies have shown that objective neurophysiological measures are sensitive to detecting concussive and subconcussive impairments in youth ice-hockey. These studies monitored brain vital signs at rink-side using a within-subjects design to demonstrate significant changes from pre-season baseline scans. However, practical clinical implementation must overcome inherent challenges related to any dependence on a baseline. This requires establishing of normative reference data sets. Methods: The current study collected specific reference data for N=58 elite, youth, male ice-hockey players and compared these with a general reference dataset from N=135 of males and females across the lifespan. The elite hockey players were recruited to a select training camp through CAA Hockey, a management agency for players drafted to leagues such as the National Hockey League (NHL). The statistical analysis included a test-retest comparison to establish reliability, and a multivariate analysis of covariance to evaluate differences in brain vital signs between groups with age as a covariate. Findings: Test-retest assessments for brain vital signs showed moderate-to-good reliability (Cronbach’s Alpha >0.7, Intraclass correlation coefficient >0.5) in 5 out of 6 measures. The multivariate analysis of covariance showed no overall effect for group (p=0.105), and a significant effect of age as a covariate was observed (p<0.001). Adjusting for the effect of age, a significant difference was observed in the measure of N100 latency (p=0.022) between elite hockey players and the general population. Interpretation: The findings support the concept that normative physiological data can be used in brain vital signs evaluation in athletes, and should additionally be stratified for age, skill level, and experience. These can be combined with general norms and/or individual baseline assessments where appropriate and/or possible. The current results allow for brain vital sign evaluation independent of baseline assessment, therefore enabling objective neurophysiological evaluation of concussion management and cognitive performance optimization in ice-hockey.